Reproductive performance of local and crossbred dairy cattle at the Asella livestock farm Arsi, Ethiopia - Negussie, E. (Alemaya University of Agriculture, 1992)
This thesis investigates the reproductive performance of local and crossbred dary cattle in Ethiopia. It is divided into five sections. The introduction in section one. Reproductive performance of local and crossbred dairy cattle and herd life are reviewed in section two. Section three covers materials and methods including: description of the study area, seasonal classification, cattle breeds and breeding program, herd management, traits studies, herd life and data recording, preparation and statistical analysis. Results and discussion on reproductive performance and herd life are discussed in section four. Section five includes summary and recommendations.